Diversity and Seasonal Variation of Avifauna along the Eastern Rapti River, Hetauda, Nepal - Pradhan, Nikeet (Banko Janakari, 2026)
Seasonal fluctuations significantly impact bird species diversity and community composition. This study was conducted in the eastern Rapti river, Nepal during winter and summer seasons to explore bird diversity in different seasons. The line transect method was adopted for this study. Altogether 21 transects were placed, and 110 bird species were recorded. According to the Shannon-Weiner diversity index, greater avian richness and diversity was recorded in the winter season than the summer season. In contrast, bird species were evenly distributed during the summer season than the winter season. The order passeriformes, and guild insectivorous had the highest number of bird species, and resident species were the most prominent. One of the notable sightings in this study was the record of Watercock (Gallicrex cinerea) for the Makwanpur District, Nepal. This study provided an overall checklist of bird species in the region, laying out baseline data on the area’s avifauna to aid and guide future studies. The Eastern Rapti river provides a unique habitat for bird species and requires a conservation management plan to protect the birds and their habitat.